Disenchantment: Liang Qichao’s Post-War European Travel and Ideological Shift - Li, Bowen (Transactions on Social Science, Education and Humanities Research, 2023)
Since the modern era, Western culture has acquired modern attributes due to its early industrialization. The political and economic systems of capitalism, and even its values, have become the aspirations of modern China. As a representative of the intellectual group learning from the West, Liang Qichao once regarded the Western capitalist society as the direction for China’s modernization. However, the outbreak of World War I changed Liang Qichao. The various contradictions in post-war Europe and the perverse actions of imperialism led Liang Qichao to deeply reflect on Western civilization. He no longer looked up to the West but instead re-examined the valuable values of Chinese civilization, establishing cultural confidence. In fact, the shift in Liang Qichao’s thinking is not an isolated case but a microcosm of the cultural awakening of the entire group of Chinese intellectuals learning from the West.